Effect of captopril on collagen metabolisms in keloid fibroblast cells. Issue 12 (23rd May 2014) - Chen, Junjie; Zhao, Sha; Liu, Yong; Cen, Ying; Nicolas, Crook
Abstract : Background: Keloid is a proliferative disease of fibrous tissues. The mechanism and consistently effective treatments of keloid remained unknown. Although there was a report about treating keloid with topical captopril, the further investigation about captopril affecting keloid has not been performed so far. Objectives: The aim of this study was to analyse the effect of captopril on collagen metabolisms in keloid fibroblast cells, and to provide information for the mechanism and therapy of keloid. Methods: To investigate the effects and relative mechanism of captopril on keloid fibroblast cells, we examined the changes of collagen metabolism, expression of angiotensin, transforming growth factor (TGF)‐β1, platelet‐derived growth factor (PDGF)‐BB and heat shock protein 47 (HSP47), and cellular proliferation in keloid fibroblast cells. Results: We found that all collagen metabolisms, expression of TGF‐β1, PDGF‐BB and HSP47, and cellular proliferation decreased significantly with effective captopril concentrations in keloid fibroblast cells. Conclusions: With a comprehensive analysis of test results, we proposed that captopril may decrease the expression of angiotensin, PDGF‐BB, TGF‐β1 and HSP47, and further inhibit proliferation and collagen synthesis of keloid fibroblast cells, which were the key in keloid formation.